Response to comment on “Oestrogen-induced angiogenesis and implantation contribute to the development of parasitic myomas after laparoscopic morcellation” - Huang, Ben-Shian (Reprod Biol Endocrinol, 2017)
According to the literature review, CO2 insufflation on parasitic myoma implantation is not well studied, and we concur that our study is related to “Morcellation-induced parasitic myomas.” We did not compare CO2 insufflation to non-insufflation in our study. The reason is the efficacy of gasless laparoscopic myomectomy and morcellation is not well established and this modality is seldom performed. Moreover, the effects of pneumoperitoneum on mesothelial cells and the role of the entire peritoneal cavity as a cofactor in adhesion formation have become well established, the role of CO2 insufflation in the establishment of parasitic myomas has not yet been studied. As such, more in-depth and well-designed studies for the role of CO2 insufflation are needed.